Black Soldier Fly (Hermetia illucens) as an Alternative Protein Source for Animal Feed - April Hari Wardhana (WARTAZOA, Indonesian Bulletin of Animal and Veterinary Sciences, 2016)
Increasing demand of protein source for animal feed, particularly fish meal and soybean meal has led to a problem in the future. It is a need to look for an alternative protein source, in order to meet amino acid requirements maintaining livestock production level. Insects possesing high quality, efficient dan rich protein content at all life stages such as Black Soldier Fly (BSF, Hermetia illucens) could be used as one of the alternatives. The flies grow and reproduce easily, have high feed efficiency and can be reared on bio-waste streams. These are neither pests nor vectors of diseases. Insect meal generally possesses levels of chemical contaminants which are below recommended maximum concentrations. The larvae have antibacterial (Escherichia coli O15:H7, Salmonella enterica serovar Enteritidis) and antiviral (enterovirus and adenovirus ) properties. Larvae of BSF could be scaled up easily and possess 40-50% protein content, including some essential amino acids that can be used to replace both fish meal and soybean meal in feed.